Brain-computer interfaces and education: the state of technology and imperatives for the future. (23rd August 2019) - Wegemer, Christopher
Progress in the field of brain-computer interfaces (BCIs) has accelerated in recent years. While the majority of research has focused on alleviating the burden of physical and psychological disabilities, use of BCI devices has expanded to a variety of applications. New educational platforms and assistive technologies have been developed to improve learning strategies and increase cognitive capabilities for both healthy and disabled individuals. This paper first reviews the BCI landscape by providing a general outline of current technology then discusses research relevant to education. The literature on educational technology is used to describe common patterns in implementation of innovations, which highlights the need for understanding complexities of educational settings and broader social contexts. In anticipation of emerging BCI technology, recommendations are made for researchers and policymakers to promote implementation strategies associated with positive academic outcomes and reduction of achievement gaps.